Development Of The Sambas State Polytechnic Campus Virtual Tour Application By Applying The Multimedia Development Life Cycle Method - Noferianto Sitompul; Vanie Wijaya; U Heri Mulyanto (Jurnal Info Sains : Informatika dan Sains, 2023)
Sambas State Polytechnic is a state university located in West Kalimantan, precisely in Sambas Regency, which is also a tertiary institution that is of interest to the people of Sambas Regency, which must have an attraction in terms of adequate information facilities. The Sambas State Polytechnic socialization (public relations) team uses PowerPoint slides, video visualization, social media, and internet media to present the Sambas State Polytechnic's profile and its nine study programs to potential high school and Madrasah Aliyah graduate students in various districts and cities in West Kalimantan Province to increase the number of students. Then, in introducing the campus area or environment to prospective students, you still need to take a manual tour around the campus area you are going to. This calls for innovation in new digital-based socialization media in the form of a virtual tour, which can accurately portray the state of the Sambas State Polytechnic, from the campus entrance to the learning support study program rooms. The virtual tour can be accessed online via a computer or mobile device, allowing people to view the original campus environment without traveling far. A virtual Tour is a digital technology innovation whose working process mechanism changes place objects or locations into digital images that can be accessed via computer devices. The Multimedia Development Life Cycle (MDLC) technique, comprising six stages—concept, design, data collecting, creation, testing, and distribution—was utilized to develop this virtual tour application. This method was chosen because it is a very familiar multimedia method for creating Virtual Tour applications. Creating this application it is hoped that it will provide benefits, namely making it easier for visitors and prospective students to get to know the Sambas State Polytechnic campus with digital simulations and implementing digital simulations on the Sambas State Polytechnic campus, which can be accessed via a web browser application.